2015
DOI: 10.1007/s00264-015-2779-6
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized clinical trial of prescription of full-time versus as-desired splint wear for de Quervain tendinopathy

Abstract: There is no difference in patient-reported outcomes and grip strength with prescription of full-time or as-desired splinting, and patients can wear the splint as they prefer. These results suggest that splinting for de Quervain tendinopathy is palliative at best and strict rest is not disease modifying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The importance of rest and immobilization in de Quervain may be less than originally theorized, particularly due to myxoid changes rather than inflammatory processes. 5 Menendez et al 17 showed that full-time splint wear versus as-desired splint wear had no effect on disability, grip strength, pain intensity, or patient satisfaction, concluding that strict rest by immobilization is not disease modifying. Our study found results to be comparable in nearly all measured outcomes between treatment groups, as well as a significantly higher prevalence of radial wrist pain in patients who received 3 weeks of immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of rest and immobilization in de Quervain may be less than originally theorized, particularly due to myxoid changes rather than inflammatory processes. 5 Menendez et al 17 showed that full-time splint wear versus as-desired splint wear had no effect on disability, grip strength, pain intensity, or patient satisfaction, concluding that strict rest by immobilization is not disease modifying. Our study found results to be comparable in nearly all measured outcomes between treatment groups, as well as a significantly higher prevalence of radial wrist pain in patients who received 3 weeks of immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of multimodal interventions compared to other intervention options may also be warranted. The outcomes from this study are promising given that orthoses alone have not demonstrated clinically important improvements in 6 weeks 56 or symptom resolution in a postpartum population. 57 Education and individualised advice may be a key component, as has been demonstrated in other musculoskeletal conditions.…”
Section: Discussionmentioning
confidence: 89%
“…Menendez et al [18] compared the effect of fulltime vs. desired time use of splinting for DS in a randomized controlled study, and they couldn't find a difference in symptom relief between two groups. We didn't compare this difference in our cohort.…”
Section: Discussionmentioning
confidence: 99%